PERUBAHAN KEBIJAKAN RENCANA ZONASI WILAYAH PESISIR DANPULAU-PULAU KECIL (RZP3K) SERTA DAMPAKNYA PADAKELOMPOK NELAYAN PULAU PARI, KEPULAUAN SERIBU SELATAN, KEPULAUAN SERIBU - Anandar, Rivanlee; Laksmono, Bambang Shergi (Jurnal Pembangunan Manusia, 2020)
The Maritime Axis proclaimed by the Jokowi-JK Government should make the coast and small islands the front yard of Indonesia. however, the condition that occurs is that the small islands in Indonesia are almost virtually untouched in terms of development because the country is focused on the land areas of the densely populated large islands. This condition can be seen from the small island community services that are far from the standards in the health sector, education, transportation, and aspects related to community needs. So far, the country's attention to small islands is under the umbrella of Law Number 1 of 2014, revised from Law Number 27 of 2007 concerning Management of Coastal Areas and Small Islands. The policy was also deemed to be unable to accommodate the needs of the small island. Currently in Indonesia has many laws and regulations governing management related to the management of coastal areas and small islands. But in reality these laws and regulations are not implemented much. This is caused by weak law enforcement, sectoral egoism and weak coordination between sectors. In managing small islands, there is often a lot of debate in terms of economic, geopolitical, and even socio-cultural. This difference in perspective leads to interventions that actually harm the island community. This happened in the Zoning Plan for Coastal Areas and Small Islands (RZWP3K) which is being prepared by the Provincial Government of DKI. One of the areas affected by the implementation of the RZWP3K is Pari Island, the Thousand Islands cluster will become a tourism island. Meanwhile, more than 300 households in Pari Island work as fishermen. The majority of this research is a study that uses a qualitative approach, with descriptive research type. The results of this study indicate that policy implementation through RZWP3K does not necessarily address the problem of space on small islands, because there are inconsistencies and uncertainty from the central and regional governments to manage and utilize coastal areas and small islands.